1994
DOI: 10.1002/rob.4620110107
|View full text |Cite
|
Sign up to set email alerts
|

Vision‐based path following by using a neural network Guidance System

Abstract: This article describes a neural network controller for guidance of a robot arm, used to model some aspects of autonomous vehicle technology. The controller uses video images with adaptive view‐angles for the sensory input, and the system was configured to simulate an autonomous vehicle guidance system on a flat terrain using a high‐contrast guiding path. To demonstrate the feasibility of using neural networks in this type of application, an Intelledex 405 robot fitted with a video camera and associated vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Van der Smagt et al [16] demonstrated visual servoing of a manipulator using a MLP capable of on-line learning using two computer workstations running in parallel. Other MLP based approaches include [17], [18], [19] and [20].…”
Section: Neural Network For Visual Positioningmentioning
confidence: 99%
“…Van der Smagt et al [16] demonstrated visual servoing of a manipulator using a MLP capable of on-line learning using two computer workstations running in parallel. Other MLP based approaches include [17], [18], [19] and [20].…”
Section: Neural Network For Visual Positioningmentioning
confidence: 99%